Medicated ocular bandages and corneal health: potential excipients and active pharmaceutical ingredients. (16th March 2018) - Zidan, Ghada; Rupenthal, Ilva D.; Greene, Carol; Seyfoddin, Ali
Abstract: Corneal blindness can occur due to improper healing of the corneal tissues after induced injury or abrasion which can be accidental, pathogenic, or after corneal surgery. Abnormal regulation of the healing mechanisms can lead to corneal opacity. Reducing inflammation and promoting epithelial wound healing are crucial for scar-free corneal recovery without eyesight complications. Current approaches for corneal wound healing involve amniotic membrane (AM) bandages, bandage contact lenses (BCL), and collagen shields in conjunction with frequent administration of therapeutic eye drops. The problem with eye drops is poor bioavailability and patient incompliance that might lead to corneal wound healing complications and poor clinical outcomes. Various methods have been proposed for loading drugs into medicated bandage lenses. There are advantages and limitations associated with each technique regarding the ease of manufacture, drug loading, release kinetics, and suitability with various therapeutics and hydrogel types. There is still, however, no drug-eluting corneal bandage on the market despite the need for such a convenient and cost-efficient strategy for corneal wound healing. This review will highlight materials and therapeutics that can be used in medicated ocular bandages and various ways of incorporating drugs, while discussing the limitations and challenges associated with bringing medicated ocular bandages in the market.